2017
DOI: 10.3892/etm.2017.4377
|View full text |Cite
|
Sign up to set email alerts
|

MRI features of growth hormone deficiency in children with short stature caused by pituitary lesions

Abstract: We verified the advantages of using magnetic resonance imaging (MRI) for improving the diagnostic quality of growth hormone deficiency (GHD) in children with short stature caused by pituitary lesions. Clinical data obtained from 577 GHD patients with short stature caused by pituitary lesions were retrospectively analyzed. There were 354 cases (61.3%) with anterior pituitary dysplasia; 45 cases (7.8%) of pituitary stalk interruption syndrome (PSIS); 15 cases (2.6%) of pituitary hyperplasia due to primary hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…Therefore, PSIS may be the most common etiology of MPHD in children and adolescents, which is different from adults [24]. Among all the non-tumor reasons, PSIS was the most common pituitary dysplasia associated with MPHD, as supported by a previous study [25]. More than 50% of the PSIS children and adolescents (61/93) had abnormal fetal positions and anoxia/asphyxia due to difficult labor.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, PSIS may be the most common etiology of MPHD in children and adolescents, which is different from adults [24]. Among all the non-tumor reasons, PSIS was the most common pituitary dysplasia associated with MPHD, as supported by a previous study [25]. More than 50% of the PSIS children and adolescents (61/93) had abnormal fetal positions and anoxia/asphyxia due to difficult labor.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, considerable variation in height has been pointed out for patients who did not receive any GH supplementation treatment (51), and some children maintain normal linear growth despite abnormal GH secretion (56). Among nearly 600 GHD patients with short stature caused by pituitary lesions, 7.8% cases of PSIS were identified in a recent study (57). In terms of treatment, growth response to GH substitution was better in the context of a pituitary defect than for isolated idiopathic GHD without any MRI abnormality (58); the most significant catch-up growth occurred before 3 years of treatment, especially during the first year of GH initiation (50).…”
Section: Hormonal Presentationmentioning
confidence: 99%
“…There is no data regarding the exact prevalence of PSIS. However, Xu et al observed PSIS in 7.8% (45/577) of cases with confirmed growth hormone deficiency (GHD) [ 16 ], while other studies have reported the condition in 4–8% of patients with hypopituitarism [ 17 , 18 ]. A male predominance is consistent with previous observations [ 19 ].…”
Section: Discussionmentioning
confidence: 99%